1990
DOI: 10.1210/mend-4-12-1827
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 11β-Hydroxysteroid Dehydrogenase Using Recombinant Vaccinia Virus

Abstract: Ligand specificity of the type I steroid receptor is apparently conferred by the activity of 11 beta-hydroxysteroid dehydrogenase. To determine the kinetic properties of this enzyme, rat liver cDNA was expressed in cultured cells using recombinant vaccinia virus. Although this enzyme catalyzes only dehydrogenation when purified from rat liver, the recombinant enzyme obtained from cell lysates catalyzed both 11 beta-dehydrogenation of corticosterone to 11-dehydrocorticosterone and the reverse 11-oxoreduction re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
67
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(73 citation statements)
references
References 17 publications
5
67
1
Order By: Relevance
“…The catalytic domain is glycosylated (13)(14)(15), which is in agreement with a lumenal orientation. Experiments to resolve the importance of glycosylation have also yielded varying results.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…The catalytic domain is glycosylated (13)(14)(15), which is in agreement with a lumenal orientation. Experiments to resolve the importance of glycosylation have also yielded varying results.…”
supporting
confidence: 64%
“…Enzymatic deglycosylation of rabbit (9) and human (13) 11␤-HSD1 has indicated that glycosylation is not important for enzyme activity. However, partial inhibition of glycosylation of the rat enzyme by tunicamycin decreased dehydrogenase activity but not reductase activity (14), and mutation of the rat (15) and human (13) sequences at putative N-glycosylation sites resulted in reduced or abolished activity.…”
mentioning
confidence: 95%
“…These results suggest that glycosylation does not significantly alter the activity of 11␤-HSD1, which is supported by the report of Ozols (9) that endo-␤-N-acetylglucosaminidase H treatment of purified 11␤-HSD1 did not significantly affect activity. On the other hand, other investigators reported decreased 11␤-HSD1 activity following incubation with tunicamycin, an inhibitor of glycosylation, or of proteins containing mutated glycosylation sites (4,64).…”
Section: Permeabilization Conditionsmentioning
confidence: 95%
“…The isoform 11␤-HSD1 is expressed in a wide array of tissues, with highest levels in the liver, from where it was purified originally (2). It catalyzes both the oxidation and reduction of glucocorticoids but acts predominantly as an oxidoreductase, thereby increasing the concentration of active glucocorticoids (3)(4)(5)(6)(7)(8). Studies on the purified protein demonstrated glycosylation and existence of a disulfide bond, suggesting that the bulk of 11␤-HSD1 is oriented to the ER lumen (9).…”
mentioning
confidence: 99%
“…Expression of a truncated form lacking the hydrophobic N-terminal part of 11P-HSDl A cDNA, and termed 11P-HSD1 B, resulted in a non-glycosylated, catalytically inactive protein species (Obeid et al, 1993), suggesting a membrane attachment and surrounding as well as glycosylation as important structural features for this class of hydroxysteroid dehydrogenases. Furthermore, tunicamycin-mediated inhibition of glycosylation resulted in a 50 % decrease of the Ilp-dehydrogenase reaction, whereas the 11-0x0 reductase reaction of heterologous expressed 11P-HSDlA rat cDNA was unaffected (Agarwal et al, 1990). The attachment of N-linked sugars to the protein could provide residues necessary for interlintrasubunit H bonding or proper orientation of the holoenzyme within the membrane environment.…”
Section: Discussionmentioning
confidence: 97%